High-strength cable and manufacturing method thereof

By using mica belt insulation layer and modified nano-silicon nitride cross-linked polyethylene protective sleeve in the cable, the aging and flammability of polyethylene cables under high temperature and vibration conditions is solved, and high strength and flame retardant performance are achieved The improvement ensures the stability and safety of the cable.

CN119252539APending Publication Date: 2025-01-03ANHUI ZHONGTONG CABLE TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411421397.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing polyethylene cables are prone to aging and damaged under high temperature and vibration conditions, and have flammable properties, which cannot meet the market's demand for high strength and flame retardant properties.

Method used

Mica tape is used as the insulating layer, and modified nano-silicon nitride is combined with low-density polyethylene to form a cross-linked protective sleeve material, improving the flame retardant and mechanical properties of the cable.

Benefits of technology

It significantly improves the flame retardant performance, mechanical strength and oxidation resistance of the cable, ensures the stability and safety of the cable, and has important application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005080900610000031
    Figure BDA0005080900610000031
  • Figure BDA0005080900610000032
    Figure BDA0005080900610000032
  • Figure BDA0005080900610000041
    Figure BDA0005080900610000041
Patent Text Reader

Abstract

The invention discloses a high-strength cable and a manufacturing method thereof, and belongs to the technical field of cables. The cable is composed of a conductor, an insulating layer and a protective sleeve which are sequentially arranged from inside to outside. The cable insulating layer is the mica tape, so that the flame retardant property of the cable is improved; the protective sleeve is made of silane crosslinked polyethylene, and compared with common polyethylene, the mechanical property of the protective sleeve is remarkably improved; compared with other cross-linking methods, the process is simple; nano silicon nitride is modified, compared with common nano silicon nitride, the compatibility with a polyethylene matrix is better, the agglomeration phenomenon is relieved, the mechanical strength, flame retardance and oxidation resistance of the cable are remarkably improved, and the cable is free of halogen and phosphorus, environmentally friendly and long and stable in performance; therefore, the prepared cable has stable and efficient flame retardance, oxidation resistance and mechanical strength, is environment-friendly and stable in performance, and has important application value in the technical field of cables.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of cables, and in particular, relates to a high-strength cable and a manufacturing method thereof. Background Art

[0002] Cables are carriers for transmitting electrical signals and electric currents. The stability of their power supply will directly determine the operating safety of the equipment. At the same time, with the development of electric energy, the application of electrical equipment is becoming more and more popular, and the performance requirements for cables are also getting higher and higher. For example, in the automotive industry, refrigeration industry, etc., cables are directly connected to the engine, and these devices are often accompanied by vibration and high temperature conditions during operation, and there is a risk of wear of the cable protective layer. At present, the cables used in such working conditions are mainly composite structures, mainly including conductive cores, insulating layers and protective sheaths. Among them, the function of the conductive core is to transmit current, and the main function of the insulating layer is to provide electrical isolation for the conductors in the cable to prevent current leakage to the surrounding environment, ensuring safe and efficient transmission of electrical energy. The protective sheath ensures the safety of power transmission and is in direct contact with the external environment, playing a decisive role in the performance of the cable.

[0003] Common cable sheath materials include polyethylene, polypropylene, fluoroplastics, chlorinated polyethers and polyamides, among which polyethylene is non-toxic, easy to shape and process, inexpensive, and has excellent comprehensive performance. It is the most widely used general-purpose plastic in the world. However, with the continuous development of productivity, the mechanical properties of the polyethylene sheath currently used are insufficient, and it is easy to age and break during use. Moreover, polyethylene has a low oxygen index and is a flammable material. It does not have flame retardant properties, and polyethylene sheath materials can no longer meet the market's usage requirements. Therefore, it is urgent to invent a high-strength and flame-retardant polyethylene cable to meet the higher demands in the field of cable technology. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a high-strength cable and a manufacturing method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A high-strength cable consists of a conductor, an insulating layer and a protective sheath which are arranged in sequence from the inside to the outside.

[0007] A method for manufacturing a high-strength cable comprises the following steps:

[0008] After the conductor is coated with an insulating layer, the protective sheath material is extruded and coated on the outer surface of the insulating layer, and cross-linked to obtain a high-strength cable.

[0009] Furthermore, the conductor is a copper conductor.

[0010] Furthermore, the insulating layer is a mica tape.

[0011] The insulation layer is mica tape, which is an excellent high temperature resistant and fire resistant insulating material with good toughness, and can enhance the flame retardant and mechanical properties of the cable.

[0012] Furthermore, the protective cover material comprises the following raw materials in parts by weight: 80-100 parts of low-density polyethylene, 5-15 parts of modified nano silicon nitride, 0.1-0.3 parts of peroxide initiator, and 3-5 parts of silane coupling agent.

[0013] Furthermore, the peroxide initiator is one of benzoyl peroxide, dicumyl peroxide, and tert-butyl perbenzoate.

[0014] Furthermore, the silane coupling agent is one of vinyltriethoxysilane and vinyltrimethoxysilane.

[0015] Furthermore, the modified nano silicon nitride is prepared by the following steps:

[0016] S1. In a three-necked flask equipped with a stirring device, 3,5-di-tert-butyl-4-hydroxybenzaldehyde, melamine and pyridine were mixed, stirred vigorously and uniformly, piperidine (condensing agent) was added, the reaction temperature was controlled to 75°C, and the reaction was kept warm for 6 hours. After the reaction was completed, the solvent was removed by vacuum distillation, washed with anhydrous ethanol 3-4 times, and vacuum dried to obtain intermediate 1; the ratio of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, melamine, pyridine and piperidine was 23.4g:13.5g:100mL:30mL;

[0017] Under the action of the condensing agent, the aldehyde group on 3,5-di-tert-butyl-4-hydroxybenzaldehyde condenses with the amino group on melamine to form an imine group (C=N Schiff base structure). By controlling the molar ratio of the two to be close to 1:1 and a slight excess of melamine, only one amino group on melamine participates in the reaction to obtain intermediate 1. The specific reaction process is as follows:

[0018]

[0019] S2. In a three-necked flask equipped with a stirring device, the intermediate 1, 9-decenoic acid and N,N-dimethylformamide (DMF) were mixed and stirred evenly, and then dicyclohexylcarbodiimide (DCC, dehydrating agent) was added, and the reaction temperature was controlled to 50°C. The reaction was kept warm for 6 hours. After the reaction was completed, it was filtered, and part of the solvent was removed by rotary evaporation. Then, it was purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 3:2), and the eluent was removed by rotary evaporation to obtain intermediate 2; the ratio of the amount of intermediate 1, 9-decenoic acid, N,N-dimethylformamide, and dicyclohexylcarbodiimide was 35.1g:17.0g:150mL:20.6g;

[0020] Under the action of DCC, intermediate 1 and 9-decenoic acid undergo amidation reaction. By controlling the molar ratio of the two to be close to 1:1 and a slight excess of intermediate 1, only one amino group on intermediate 1 participates in the reaction to obtain intermediate 2. The specific reaction process is as follows:

[0021]

[0022] S3, add glutaric acid, intermediate 2, dicyclohexylcarbodiimide and toluene to a three-necked flask equipped with a stirring device, stir and mix well, place in a 55°C water bath, heat in a water bath for 8 hours, filter after the reaction, remove the solvent by vacuum distillation, and purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, the volume ratio of the two is 4:3), remove the eluent by rotary evaporation to obtain intermediate 3; the ratio of glutaric acid, intermediate 2, dicyclohexylcarbodiimide and toluene is 14.7g:49.4g:20.6g:150mL;

[0023] Glutaric acid undergoes an amidation reaction with intermediate 2, and under the action of dicyclohexylcarbodiimide, the reaction can be carried out under relatively mild conditions to obtain intermediate 3; the specific reaction process is as follows:

[0024]

[0025] S4. Add nano silicon nitride and toluene to a three-necked flask, stir magnetically for 2 hours to make the nano silicon nitride evenly dispersed, then add intermediate 3, dicyclohexylcarbodiimide and 4-dimethylaminopyridine, start stirring, react at 70°C for 12 hours, and after the reaction is completed, filter out the residue, wash it with anhydrous ethanol 3-4 times, vacuum dry it, and grind it to obtain modified nano silicon nitride; the ratio of nano silicon nitride, toluene, intermediate 3, dicyclohexylcarbodiimide and 4-dimethylaminopyridine is 5g:100mL:10g:15g:0.2g;

[0026] The surface of nano-silicon nitride contains a large amount of -OH and -NH2, which can react with the carboxyl group on the intermediate 3 under the catalysis of dicyclohexylcarbodiimide and 4-dimethylaminopyridine to obtain modified nano-silicon nitride;

[0027] Nano silicon nitride is a ceramic powder with excellent performance, good high temperature strength, high fracture strength, high hardness, excellent friction and wear resistance. Nano silicon nitride is grafted with organic molecular chains through chemical bonding, that is, an organic layer is formed on its surface, which improves the surface hydrophobicity of nano silicon nitride, greatly improves the interface compatibility between nano silicon nitride and polyethylene matrix, reduces the agglomeration of nano silicon nitride, and promotes the uniform dispersion of modified nano silicon nitride in the matrix, greatly improves the mechanical strength of the matrix, and the grafted organic molecular chains can effectively prevent the migration and shedding of organic molecules; not only that, the modified nano silicon nitride also contains hindered phenol, Schiff base, triazine and long carbon chain structure; among them, the structure of hindered phenol can provide active hydrogen Atoms can capture peroxyl radicals, which can not only improve the antioxidant property of the matrix, but also act as an antioxidant in the refining process, avoiding the addition of additional antioxidants and affecting the homogeneity of the protective cover material. In addition, the C=N double bond in the Schiff base structure can generate a carbon-nitrogen six-membered ring at high temperature. This type of six-membered ring structure enables the matrix to form a stable cross-linked network, effectively improving the flame retardant properties of the matrix. In addition, the introduced triazine structure will produce nitrogen-containing gas during combustion, which will dilute and reduce the smoke density, and self-condense at high temperature to form melem to make the carbon layer compact, further improving the flame retardant properties of the matrix. Finally, the introduced long carbon chain is a methylene chain segment, which is a flexible chain segment and can be interspersed in the cross-linked structure of the matrix, which not only improves the mechanical properties of the matrix, but also improves the stability of the performance.

[0028] It should be noted that one end of the modified nano-silicon nitride also contains a carbon-carbon double bond, which can be cross-linked with the matrix, thereby enhancing the interaction force with the matrix and improving the long-term stability of the modified nano-silicon nitride performance.

[0029] Beneficial effects of the present invention:

[0030] 1. The cable insulation layer prepared by the present invention is a mica tape, which improves the flame retardant performance of the cable;

[0031] 2. The protective cover material is silane cross-linked polyethylene, which changes the linear polyethylene into a cross-linked polyethylene with a three-dimensional silicon network structure. Compared with ordinary polyethylene, the mechanical properties have been significantly improved; and compared with other cross-linking methods, the process is simple and the cost of production equipment is low;

[0032] 3. By modifying nano silicon nitride, compared with ordinary nano silicon nitride, it has better compatibility with polyethylene matrix, reduces agglomeration, significantly improves the mechanical strength, flame retardancy and oxidation resistance of the cable, and is halogen-free and phosphorus-free, environmentally friendly, and has long-term stable performance;

[0033] Therefore, the cable prepared by the present invention has stable and efficient flame retardancy, oxidation resistance and mechanical strength, is environmentally friendly, has stable performance, and has important application value in the field of cable technology. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] Preparation of modified nano silicon nitride:

[0037] S1. In a three-necked flask equipped with a stirring device, 23.4 g of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, 13.5 g of melamine and 100 mL of pyridine were mixed, and after vigorous stirring, 30 mL of piperidine was added, and the reaction temperature was controlled to 75°C. The reaction was kept warm for 6 hours. After the reaction was completed, the solvent was removed by reduced pressure distillation, and the mixture was washed with anhydrous ethanol for 3 times, and vacuum dried to obtain intermediate 1;

[0038] S2. In a three-necked flask equipped with a stirring device, 35.1 g of intermediate 1, 17.0 g of 9-decenoic acid and 150 mL of N,N-dimethylformamide were mixed and stirred evenly, and then 20.6 g of dicyclohexylcarbodiimide was added. The reaction temperature was controlled to 50 ° C. The reaction was kept warm for 6 hours. After the reaction was completed, it was filtered, and part of the solvent was removed by rotary evaporation. Then, it was purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 3:2), and the eluent was removed by rotary evaporation to obtain intermediate 2;

[0039] S3, in a three-necked flask equipped with a stirring device, add 14.7 g of glutaric acid, 49.4 g of intermediate 2, 20.6 g of dicyclohexylcarbodiimide and 150 mL of toluene, stir and mix well, place in a 55°C water bath, heat in a water bath for 8 h, filter after the reaction, remove the solvent by vacuum distillation, and purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, the volume ratio of the two is 4:3), and remove the eluent by rotary evaporation to obtain intermediate 3;

[0040] S4. Add 5 g of nano silicon nitride and 100 mL of toluene into a three-necked flask, stir magnetically for 2 h to evenly disperse the nano silicon nitride, then add 10 g of intermediate 3, 15 g of dicyclohexylcarbodiimide and 0.2 g of 4-dimethylaminopyridine, start stirring, and react at 70 °C for 12 h. After the reaction is complete, filter out the residue, wash it three times with anhydrous ethanol, dry it in vacuo, and grind it to obtain modified nano silicon nitride.

[0041] Example 2

[0042] Preparation of modified nano silicon nitride:

[0043] S1. In a three-necked flask equipped with a stirring device, 46.8 g of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, 27.0 g of melamine and 200 mL of pyridine were mixed, and after vigorous stirring, 60 mL of piperidine was added, and the reaction temperature was controlled to 75° C. The reaction was kept warm for 6 hours. After the reaction was completed, the solvent was removed by reduced pressure distillation, and the mixture was washed with anhydrous ethanol for 4 times and dried in vacuo to obtain intermediate 1;

[0044] S2. In a three-necked flask equipped with a stirring device, 70.2 g of intermediate 1, 34.0 g of 9-decenoic acid and 300 mL of N, N-dimethylformamide were mixed and stirred evenly, and then 41.2 g of dicyclohexylcarbodiimide was added, and the reaction temperature was controlled to 50 ° C. The reaction was kept warm for 6 hours. After the reaction was completed, it was filtered, and part of the solvent was removed by rotary evaporation. Then, it was purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 3:2), and the eluent was removed by rotary evaporation to obtain intermediate 2;

[0045] S3, in a three-necked flask equipped with a stirring device, add 29.4 g of glutaric acid, 98.8 g of intermediate 2, 41.2 g of dicyclohexylcarbodiimide and 300 mL of toluene, stir and mix well, place in a 55°C water bath, heat in a water bath for 8 h, filter after the reaction, remove the solvent by vacuum distillation, and purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, the volume ratio of the two is 4:3), and remove the eluent by rotary evaporation to obtain intermediate 3;

[0046] S4. Add 10 g of nano silicon nitride and 200 mL of toluene into a three-necked flask, stir magnetically for 2 h to evenly disperse the nano silicon nitride, then add 20 g of intermediate 3, 30 g of dicyclohexylcarbodiimide and 0.4 g of 4-dimethylaminopyridine, start stirring, and react at 70 °C for 12 h. After the reaction is complete, filter out the residue, wash it four times with anhydrous ethanol, dry it in vacuo, and grind it to obtain modified nano silicon nitride.

[0047] Example 3

[0048] Preparation of protective cover materials:

[0049] 80g of low-density polyethylene was dried in an oven for 12h, and the dried low-density polyethylene, 5g of modified nano-silicon nitride obtained in Example 1, 0.1g of benzoyl peroxide, and 3g of vinyltrimethoxysilane were mixed and stirred evenly, added to a twin-screw extruder, melt blended, extruded to form a sheet, and cross-linked under boiling conditions at 80°C for 8h to form a sheath material.

[0050] Example 4

[0051] Preparation of protective cover materials:

[0052] 90 g of low-density polyethylene was dried in an oven for 18 h, and the dried low-density polyethylene, 10 g of modified nano-silicon nitride obtained in Example 2, 0.2 g of diisopropylbenzene peroxide, and 4 g of vinyltriethoxysilane were mixed and stirred evenly, added to a twin-screw extruder, melt-blended, extruded to form a sheet, and cross-linked under boiling conditions at 85° C. for 10 h to form a sheath material.

[0053] Example 5

[0054] Preparation of protective cover materials:

[0055] 100 g of low-density polyethylene was dried in an oven for 24 h, and the dried low-density polyethylene, 15 g of modified nano-silicon nitride obtained in Example 2, 0.3 g of tert-butyl perbenzoate, and 5 g of vinyltriethoxysilane were mixed and stirred evenly, added to a twin-screw extruder, melt blended, extruded, and made into a sheet, which was cross-linked under boiling conditions at 90° C. for 12 h to make a sheath material.

[0056] Example 6

[0057] The copper conductor is coated with mica tape to form an insulating layer; 100g of low-density polyethylene is dried in an oven for 24h, then mixed and stirred evenly with 15g of modified nano silicon nitride prepared in Example 2, 0.3g of tert-butyl perbenzoate, and 5g of vinyl triethoxysilane, added into a twin-screw extruder, melt blended, and then coated on the outer surface of the insulating layer through an extruder, and then cross-linked under 90°C boiling conditions for 12h to obtain a high-strength cable.

[0058] Comparative Example 1

[0059] Ordinary nano silicon nitride is used to replace the modified nano silicon nitride in Example 5, and the remaining steps are the same as those in Example 5 to obtain the sheath material.

[0060] Comparative Example 2

[0061] A commercially available high-strength flame-retardant radiation cross-linked polyethylene cable material produced by Henan Anerxin Polymer Materials Co., Ltd. was used.

[0062] The protective cover materials of Examples 3-5 and Comparative Examples 1-2 were made into corresponding shapes to be tested according to different test standards, and the following performance tests were performed:

[0063] The national standard GB / T 2406-2008 "Test method for combustion performance of plastics" is used to determine the limiting oxygen index;

[0064] The oxidation induction time of the sample was determined using the national standard GB / T 19466.6-2009 "Plastic Differential Scanning Calorimetry";

[0065] The national standard GB / T 1040.2-2006 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics" and the national standard GB / T 1043.1-2008 "Determination of impact properties of simply supported beams of plastics Part 1: Non-instrumented impact test" were used to measure the tensile properties and impact resistance of the samples before and after being placed at room temperature for 180 days;

[0066] The measured results are shown in the following table:

[0067]

[0068] It can be seen from the above table that the flame retardancy, oxidation resistance and mechanical strength of the protective sheath material prepared in the embodiment of the present invention are higher than those of the comparative example, and the performance is long-lasting and stable. The cable made of the protective sheath material has high strength and has important application value in the field of cable technology.

[0069] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0070] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A high-strength cable, consisting of a conductor, an insulating layer and a protective sheath arranged in sequence from the inside to the outside, characterized in that: The protective cover material comprises the following raw materials in parts by weight: 80-100 parts of low-density polyethylene, 5-15 parts of modified nano silicon nitride, 0.1-0.3 parts of peroxide initiator, and 3-5 parts of silane coupling agent; Wherein, the modified nano silicon nitride is prepared by the following steps: S1. Mix 3,5-di-tert-butyl-4-hydroxybenzaldehyde, melamine and pyridine, stir evenly, add piperidine, react at 75° C. for 6 h, and after the reaction is complete, distill under reduced pressure, wash, and dry to obtain intermediate 1; S2, mixing the intermediate 1, 9-decenoic acid and N,N-dimethylformamide, adding dicyclohexylcarbodiimide, reacting at 50°C for 6h, filtering, rotary evaporating, column chromatography purification, and rotary evaporating to obtain the intermediate 2; S3, glutaric acid, intermediate 2, dicyclohexylcarbodiimide and toluene were stirred and mixed uniformly, and then heated in a water bath at 55° C. for 8 h. After the reaction was completed, the mixture was filtered, distilled under reduced pressure, purified by column chromatography, and rotary evaporated to obtain intermediate 3; S4. Add nano silicon nitride and toluene into a three-necked flask, stir for 2 hours, then add intermediate 3, dicyclohexylcarbodiimide and 4-dimethylaminopyridine, start stirring, react at 70°C for 12 hours, and after the reaction is completed, filter, wash, dry and grind to obtain modified nano silicon nitride.

2. A high-strength cable according to claim 1, characterized in that: In step S1, the ratio of the amount of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, melamine, pyridine and piperidine is 23.4 g:13.5 g:100 mL:30 mL.

3. A high-strength cable according to claim 1, characterized in that: In step S2, the ratio of the amount of intermediate 1, 9-decenoic acid, N,N-dimethylformamide, and dicyclohexylcarbodiimide is 35.1 g:17.0 g:150 mL:20.6 g.

4. A high-strength cable according to claim 1, characterized in that: In step S3, the ratio of glutaric acid, intermediate 2, dicyclohexylcarbodiimide and toluene is 14.7 g:49.4 g:20.6 g:150 mL.

5. A high-strength cable according to claim 1, characterized in that: In step S4, the ratio of the amount of nano-silicon nitride, toluene, intermediate 3, dicyclohexylcarbodiimide, and 4-dimethylaminopyridine is 5g:100mL:10g:15g:0.2g.

6. A high-strength cable according to claim 1, characterized in that: The peroxide initiator is one of benzoyl peroxide, dicumyl peroxide and tert-butyl perbenzoate.

7. A high-strength cable according to claim 1, characterized in that: The silane coupling agent is one of vinyl triethoxy silane and vinyl trimethoxy silane.

8. The method for manufacturing a high-strength cable according to claim 1, characterized in that: The following steps are involved: After the conductor is coated with an insulating layer, the protective sheath material is extruded and coated on the outer surface of the insulating layer, and cross-linked to obtain a high-strength cable.